Specific accounting standards for waqf institutions: the impact of its non-existence to waqf accounting practices in Malaysia / Norlaila Yusof - Yusof, Norlaila (Universiti Teknologi MARA, 2021)
The purpose of accounting standard is to govern the accounting process and subsequently reporting for entities. Hence, the absence of a specific accounting standard to govern the accounting for an entity would be problematic and would give rise to several issues. This research aims to understand how the absence of a specific accounting standard affects the accounting practices of an entity. The findings show how the waqf corporation tries to adhere to the prevailing accounting standard, which is not specific for waqf institutions, and how important it is to have a specific accounting standard in place for waqf institutions.